CeO2−x quantum dots with massive oxygen vacancies as efficient catalysts for the synthesis of dimethyl carbonate. Issue 3 (10th December 2019) - Wang, Zhi-Qiao; Zhang, Ming-Jian; Hu, Xiao-Bing; Dravid, Vinayak P.; Xu, Zhong-Ning; Guo, Guo-Cong
Abstract : CeO2– x quantum dots with massive oxygen vacancies are obtained by a one-step single molecular synthesis strategy. The yield of dimethyl carbonate from CO2 and methanol is more than 5 times that for commercial CeO2 nanoparticles. Abstract : CeO2− x quantum dots with massive oxygen vacancies are obtained by a one-step single molecular synthesis strategy. The yield of dimethyl carbonate from CO2 and methanol is more than 5 times that for commercial CeO2 nanoparticles.